iTAP, a novel iRhom interactor, controls TNF secretion by policing the stability of iRhom/TACE - Oikonomidi, Ioanna (2019)
The apical inflammatory cytokine TNF regulates numerous important biological processes including inflammation and cell death, and drives inflammatory diseases. TNF secretion requires TACE (also called ADAM17), which cleaves TNF from its transmembrane tether. The trafficking of TACE to the cell surface, and stimulation of its proteolytic activity, depends on membrane proteins, called iRhoms. To delineate how the TNF/TACE/iRhom axis is regulated, we performed an immunoprecipitation/mass spectrometry screen to identify iRhom-binding proteins. This identified a novel protein, that we name iTAP (iRhom Tail-Associated Protein) that binds to iRhoms, enhancing the cell surface stability of iRhoms and TACE, preventing their degradation in lysosomes. Depleting iTAP in primary human macrophages profoundly impaired TNF production and tissues from iTAP KO mice exhibit a pronounced depletion in active TACE levels. Our work identifies iTAP as a physiological regulator of TNF signalling and a novel target for the control of inflammation.